Iron (Fe) dissolved in soil pore water measured at various locations within the drained thaw lake basin near Barrow, Alaska, 2012 ... - Miller, K.; Friedman, E.; Angenent, L.; Lipson, D. (NSF Arctic Data Center, 2013)
In 2012, iron (Fe) dissolved in soil pore water was measured at various locations within the drained thaw lake basin previously used for the Biocomplexity Experiment (BE), near Barrow, Alaska (AK). Collars were arranged in three clusters within the central region of the BE, referred to as A, B and C. Soil water was sampled with Rhizon water samplers, preserved with hydrochloric acid (HCl) and analyzed colorimetrically with 1,10-phenanthroline. ...